The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1111/ped.14152
|View full text |Cite
|
Sign up to set email alerts
|

Employment status and contributing factors among adults with congenital heart disease in Japan

Abstract: Background Working is an important concern in transitional care for adults with congenital heart disease (ACHD) because work connects people with society. Employment status is correlated with gender, but studies on patient employment by gender have rarely been conducted. This study therefore aimed to examine the employment status of ACHD by gender and to explore the factors influencing this status. Methods In this study, 193 Japanese ACHD (mean age: men—33.62 years, women—32.69 years; 89 men, no students inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Moreover, patients with congenital heart disease use to have lower educational levels in addition to being less likely employed than healthy controls (Crossland et al, 2005;Sluman et al, 2019;Cocomello et al, 2021, Olsen et al, 2011 which may also be a contributing factor to mobbing. Therefore, as a higher educational level generally leads to jobs with less physical work, more internal and external recovery possibilities, and, often, better job conditions which is beneficial for patients with congenital heart defects (Zomer et al, 2012) efforts should be undertaken to maximize academic fulfillment in this population as many of them fail to enter or to remain in the labor market because of a lack of studies, skills, or due to skills mismatches (Enomoto et al, 2020;Karsenty et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with congenital heart disease use to have lower educational levels in addition to being less likely employed than healthy controls (Crossland et al, 2005;Sluman et al, 2019;Cocomello et al, 2021, Olsen et al, 2011 which may also be a contributing factor to mobbing. Therefore, as a higher educational level generally leads to jobs with less physical work, more internal and external recovery possibilities, and, often, better job conditions which is beneficial for patients with congenital heart defects (Zomer et al, 2012) efforts should be undertaken to maximize academic fulfillment in this population as many of them fail to enter or to remain in the labor market because of a lack of studies, skills, or due to skills mismatches (Enomoto et al, 2020;Karsenty et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…11 There were only a few studies of transitional care in Japan, mainly in the field of cardiology. 12,13 Recently, several articles in nephrology, endocrinology, and gastroenterology have also been published, especially after 2020. [14][15][16][17][18][19] Many of them reported that there was insufficient awareness of transitional care among patients, families, and adult physicians, and that they should work together to facilitate transitional care in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the Japan Pediatric Society 10 After this, systems and tools for specialized care were also developed 11 . There were only a few studies of transitional care in Japan, mainly in the field of cardiology 12,13 14–19 .…”
Section: Introductionmentioning
confidence: 99%